The Complexity of the Definition of Terrorism In The United States:How Terrorism Is Understood In The United States and Who IsWorthy of Being Called A TerroristIn The American Perspective - Dewi, Chika (Journal of Terrorism Studies, 2019)
The definition of terrorism, in general, is an act that is against the law or action that can be against the community and when it is planned to achieve political or religious goals. Initially, the resolution of terrorism was still national related to political struggles in countries where the government system was weak and the democratic politics were still fragile, such as in Colombo, Nepal, Syria, Somalia, Sudan, and other related countries in sub-Saharan Africa. After the events of 11 September 2001 in New York and Washington D.C. has made the issue of terrorism placed high on the international agenda. This change occurred because the events of 9/11 had befallen the United States. The United States is a country with an international system that requires US national security. The existence of 9/11 also caused complexity or complexity in resolving terrorism and who deserves to be approved as a terrorist in the United States context. This complexity occurs because of the difficulty in determining who, by whom, and for what acts of terrorism are carried out. Therefore, in this paper, a further study will be carried out on the complexity of the definition of terrorism in the United States and who deserves to be called a terrorist according to the United States version. To analyses the problem in this study, the authors used constructivism and the research method used was a qualitative research method.